Phenolic Profile, Antioxidant Activity, and Enzyme Inhibitory Properties of Limonium delicatulum (Girard) Kuntze and Limonium quesadense Erben - A. Ruiz-Riaguas; G. Zengin; K.I. Sinan; C. Salazar-Mendías; E.J. Llorent-Martínez (Journal of Chemistry)
In this work, we report the phytochemical composition and bioactive potential of methanolic and aqueous extracts of leaves from Limonium delicatulum (Girard) Kuntze and Limonium quesadense Erben. The characterization and quantitation of individual phytochemicals were performed with liquid chromatography with diode array and electrospray-tandem mass spectrometry detection. Myricetin glycosides were abundant in L. delicatulum, whereas L. quesadense was rich in gallo(epi)catechin-O-gallate. Total phenolics, flavonols, and flavonoids were assayed with conventional methods. Antioxidant and radical scavenging assays (phosphomolybdenum, DPPH, ABTS, CUPRAC, FRAP, and metal chelating activity), as well as enzyme inhibitory assays (acetylcholinesterase, butyrylcholinesterase, tyrosinase, amylase, glucosidase, and lipase), were performed to evaluate the potential bioactivity. The methanolic extracts of both species presented higher phenolic content and bioactivity than the aqueous extracts. Overall, L. quesadense extracts exhibited the most potent activity for most assays, representing a potential source of bioactive compounds for the pharmaceutical and food industries.